PEMBUATAN CREAM DETERGENT UNTUK MENINGKATKAN KETRAMPILAN IBU-IBU PKK - Kusumayanti, Heny; Budiyono, Budiyono; Dwimawanti, Ida Hayu; Yesiana, Reny; Purwanto, Agus; Subari, Arkhan (Gema Teknologi, 2018)
Cream detergent is often used in everyday life, serves to wash and clean the dirt (fat). In order to commemorate the day of kartini in 2018, held a training on making cream detergent in Kp. Krapyak RT 07 RW 11 Bintoro Demak. The pH cream detergent generated from this training is 11, this is in accordance with SNI 0062: 2016, where the pH max cream detergent is 11. The purpose of this devotion provides the transfer of science and technology appropriately to the mother of PKK and also to provide skills and entrepreneurship to PKK mothers.